2018
DOI: 10.1016/j.bbi.2018.03.003
|View full text |Cite|
|
Sign up to set email alerts
|

Insight meditation and telomere biology: The effects of intensive retreat and the moderating role of personality

Abstract: A growing body of evidence suggests that meditation training may have a range of salubrious effects, including improved telomere regulation. Telomeres and the enzyme telomerase interact with a variety of molecular components to regulate cell-cycle signaling cascades, and are implicated in pathways linking psychological stress to disease. We investigated the effects of intensive meditation practice on these biomarkers by measuring changes in telomere length (TL), telomerase activity (TA), and telomere-related g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 85 publications
6
48
1
Order By: Relevance
“…The stress resulting from fear tends to diminish resilience (McEwen 2016), which is of course particularly needed during the spread of a highly infectious disease like COVID-19. Here, mindfulness practice might offer a tool to strengthen the immune system (Kaliman et al 2014; see also Conklin et al 2018 on the effect of intense mindfulness meditation on telomere biology). From this perspective, facing fear with mindfulness can be expected to have not only immediate (and long-term) beneficial effects on the mind but also on the body, in line with a recurrent pattern evident in some of the material surveyed above.…”
Section: Fear and Covid-19mentioning
confidence: 99%
“…The stress resulting from fear tends to diminish resilience (McEwen 2016), which is of course particularly needed during the spread of a highly infectious disease like COVID-19. Here, mindfulness practice might offer a tool to strengthen the immune system (Kaliman et al 2014; see also Conklin et al 2018 on the effect of intense mindfulness meditation on telomere biology). From this perspective, facing fear with mindfulness can be expected to have not only immediate (and long-term) beneficial effects on the mind but also on the body, in line with a recurrent pattern evident in some of the material surveyed above.…”
Section: Fear and Covid-19mentioning
confidence: 99%
“…First, we cannot preclude in the controls that other genes undergo changes in DNA methylation levels in relation to telomere length, since we have studied a very small number of genes. Second, these genes were found to be differentially methylated in meditation practitioners and meditation may be related to the maintenance of telomere length [12][13][14][15][16] . Thus, finding a relationship between methylation of these genes and telomere length is interesting and opens up the venue to further study these genes as targets of epigenetic changes in meditation practitioners.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it has been proposed that meditation techniques could positively affect longevity 9,10 . In fact, intensive meditation training has been associated with an increase in telomerase activity 11 and longer telomere length in blood cells [12][13][14][15][16] , which is considered a candidate biomarker of human aging.…”
mentioning
confidence: 99%
“…We retained 68% of the participants from baseline to post and 47% of the participants from baseline through to the 2-month follow-up, compared with an average retention rate of between 57% and 77% for other yoga or mindfulness retreat studies. 57,58 One reason for our slightly lower retention rates could be that frontline professionals are more prone to stress and compassion fatigue than the general population, which may have corresponded with a decreased likelihood of completing the later surveys. Indeed, we observed that participants who only completed the baseline survey reported higher levels of stress and negative affect than participants who also completed the other surveys.…”
Section: Fig 2 (Continued)mentioning
confidence: 98%